2015
DOI: 10.1038/pr.2015.155
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile in newborn rat lungs after two days of recovery of mechanical ventilation

Abstract: Background: Preterm infants having immature lungs often require respiratory support, potentially leading to bronchopulmonary dysplasia (BPD). Conventional BPD rodent models based on mechanical ventilation (MV) present outcome measured at the end of the ventilation period. A reversible intubation and ventilation model in newborn rats recently allowed discovering that different sets of genes modified their expression related to time after MV. In a newborn rat model, the expression profile 48 h after MV was analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
(42 reference statements)
2
4
0
Order By: Relevance
“…Additionally, we see major dysregulation of proteins associated with immune effector processes including complement pathway proteins, which is consistent with a previous animal study that identified increased expression of complement components in a newborn rat lung injury model [26]. Of interest, blood coagulation and fibrin clot formation pathways were associated with proteins with statistically significant changes in abundance in our urine proteomics study.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, we see major dysregulation of proteins associated with immune effector processes including complement pathway proteins, which is consistent with a previous animal study that identified increased expression of complement components in a newborn rat lung injury model [26]. Of interest, blood coagulation and fibrin clot formation pathways were associated with proteins with statistically significant changes in abundance in our urine proteomics study.…”
Section: Discussionsupporting
confidence: 91%
“…However, in a study in lung tissue from mechanically ventilated newborn rats with 60% oxygen treatment and LPS-injections, the authors found differentially regulated genes from the immune system, inflammatory response and hematopoiesis, similar to our findings, but after only 6 hours of treatment with oxygen 27 .…”
Section: Hyperoxia and Gene Regulationsupporting
confidence: 90%
“…Similar studies have been undertaken during lung development in rhesus macaques, to highlight cross talk of dynamic functional modules (groups of genes in regulatory networks) during primate lung development (586). Pathological changes to transcriptome were assessed in lungs from rat pups that received intraperitoneal E. coli 026:B6 followed by a period of mechanical ventilation (130). A microarray analysis of the lung transcriptome revealed alternations to MMP expression and the complement system, identifying MMP and complement-mediated pathways as candidate pathogenic factors in the associated lung pathology.…”
Section: L1123mentioning
confidence: 99%